Efforts to Create an Interesting and Meaningful Physics Learning Environment with a Project-Based Learning Model - Rizaldi, Dedi Riyan; Ziadatul Fatimah (AMPLITUDO : Journal of Science and Technology Innovation, 2023)
The rapid development of the times will certainly bring up new skills, especially in the era of the Industrial Revolution 4.0 and Society 5.0, which are currently developing. Digital technology is the most important part in building this era. So that this era makes internet-based technology a human companion to carry out their daily activities. With the new environment, of course, the world of education as one part that plays a role in producing human resources must be wise in creating meaningful learning conditions. The condition of a meaningful learning environment is needed in almost all subjects, including physics. One of the learning models that can change or modify the student learning environment is to apply a project-based learning model (PjBL) with six stages, namely: 1) Start with the Essential Question; 2) Design a Plan for the Project; 3) Create a Schedule; 4) Monitor the Student and the Progress of Project; 5) Assess the Outcome; and 6) Evaluate the Experience. The application of the project-based PjBL model received a positive response from students at MA Plus Nurul Islam Sekarbela, this was reinforced by the percentage of student interest in project-based physics learning, which was 55.55% in the "very interesting" category and 26.98% in the "interesting" category, so that by using the model PjBL makes students feel very interested in learning by producing a product, namely student worksheets and learning videos "Physics Experiments" which can be used as guides for other students in need